Estimation and inference for varying-coeffcient models with nonstationary regressors using penalized splines - Haiqiang Chen; Ying Fang; Yingxing Li (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
This paper considers estimation and inference for varying-coefficient models with nonstationary regressors. We propose a nonparametric estimation method using penalized splines, which achieves the same optimal convergence rate as kernel-based methods, but enjoys computation advantages. Utilizing the mixed model representation of penalized splines, we develop a likelihood ratio test statistic for checking the stability of the regression coefficients. We derive both the exact and the asymptotic null distributions of this test statistic. We also demonstrate its optimality by examining its local power performance. These theoretical fundings are well supported by simulation studies.
Keywords: C12; C14; C22; 330; Nonstationary Time Series; Varying-coefficient Model; Likelihood Ratio Test; Penalized Splines